2017
DOI: 10.1038/onc.2017.342
|View full text |Cite
|
Sign up to set email alerts
|

Coactosin-like protein CLP/Cotl1 suppresses breast cancer growth through activation of IL-24/PERP and inhibition of non-canonical TGFβ signaling

Abstract: Coactosin-like protein (CLP, or Cotl1), is an F-actin-binding protein, whose role in cancer is largely unknown. Here we show that CLP/Cotl1 is highly expressed in a rat epithelial breast cancer cell line (FE1.3) compared with its mesenchymal counterpart (FE1.2). Knockdown of CLP/Cotl1 in FE1.3 cells increased cell proliferation, whereas its overexpression in FE1.2 cells inhibited proliferation in culture and reduced tumor growth in xenograft assays in mice. Mechanistically, we identified two major pathways thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Previous studies have shown that HIF-1α and VEGF-A can be induced through ERK1/2, PI3K/AKT, STAT3, and JNK pathways 19 22 . Thus, we also analyzed the expression of these proteins in tumor cell supernatant pre-treated HUVECs, and the results showed that low levels of pERK and pAKT were observed in HUVEC-SW1116/CCL19-CM compared with HUVEC-SW1116/Vector-CM, as well as high levels of pERK and pAKT were found in HUVEC-SW620/sh-CCL19-CM compared with HUVEC-SW620/sh-NC-CM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that HIF-1α and VEGF-A can be induced through ERK1/2, PI3K/AKT, STAT3, and JNK pathways 19 22 . Thus, we also analyzed the expression of these proteins in tumor cell supernatant pre-treated HUVECs, and the results showed that low levels of pERK and pAKT were observed in HUVEC-SW1116/CCL19-CM compared with HUVEC-SW1116/Vector-CM, as well as high levels of pERK and pAKT were found in HUVEC-SW620/sh-CCL19-CM compared with HUVEC-SW620/sh-NC-CM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 25 CLP/COTL1 is highly expressed in a rat epithelial breast cancer cell line (FE1.3) compared with its mesenchymal counterpart (FE1.2). 19 Knockdown of COTL1 in FE1.3 cells promoted cell proliferation, whereas its overexpression in FE1.2 cells inhibited proliferation and reduced tumor growth in xenograft assays. 19 Therefore, we speculated that COTL1 might be important in GBM progression.…”
Section: Discussionmentioning
confidence: 94%
“… 19 Knockdown of COTL1 in FE1.3 cells promoted cell proliferation, whereas its overexpression in FE1.2 cells inhibited proliferation and reduced tumor growth in xenograft assays. 19 Therefore, we speculated that COTL1 might be important in GBM progression. By conducting colony formation and MTT assays, we observed COTL1 inhibited GBM cell proliferation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…11,12 It was described to act as tumor suppressor in early carcinogenesis by inducing apoptosis or inhibiting cell growth, while promoting tumorigenicity and metastasis through suppression of local immunosurveillance and supporting tumor progression in advanced stages of cancer. 13,14 Located on chromosome 19 (19q13.1), TGFB1 gene contains several functional and non-functional polymorphisms, some of which were shown to contribute to altered BC susceptibility. 7,[15][16][17][18] Of these, rs1800469 (-1347C.T) promoter, rs1800470 (+29T.C) codon 10, and rs1800471 (+74G.C) signal peptide sequence variants were widely studied in BC.…”
Section: Introductionmentioning
confidence: 99%